Dimensionless models of representative parameters of the spray obtained from effervescent atomizers - Amaro, Jordan [UNESP]; Gamboa, Alexander R. [UNESP]; Mendiburu, Andrés Z.; dos Santos, Leila Ribeiro; de Carvalho, João A. [UNESP] (Springer Nature, 2023)
The goal of this study was to develop dimensionless models to estimate characteristic parameters associated with the atomization of light heating oil in effervescent atomizers. Parameters like the integral Sauter mean diameter (ID32), the spray cone half-angle (γ/2) and the liquid concentration half-angle (α/2) are considered. An analytical method was developed to determine the coefficient and exponents of an optimized dimensionless model. A total of seven dimensionless models (M1 – M7) were taken into consideration, from which seven models (M1 – M7) were used to estimate ID32, and five models (M3 – M7) were used to estimate γ/2 and α/2. In order to establish each set of models (M1 – M7 and M3 – M7), a total of 255 experimental results obtained from 34 effervescent atomizers of the outside-in gas injection configuration were used. The model M3 was selected to estimate ID32, γ/2 and α/2, returning values of R2 equal to 0.895, 0.762 and 0.809, respectively. The dimensionless models showed very good accuracy; therefore, the analytical method developed to propose dimensionless models is also validated.
Keywords: Atomization; Dimensional analysis; Light heating oil (LHO); Model; Spray